Pedagogical Preparation for Physical Training and Its Cultural Aspect - Garalis, Algirdas (Acta Paedagogica Vilnensia, 1997)
The article is about the importance of physical training for the development of the personality in the overall cultural context. Much attention is given to the historical aspect of physical training, the experience of the ancient Greeks, and the period between the civil wars of Lithuania. The article discloses the importance of physical training for the development of the personality and the evolution of the culture. A concern is expressed about the current situation of the preparation of specialists. It is very important that a teacher of physical training not be limited to the perfection of narrow innate human possibilities. He or she should develop an intelligent personhood and be a citizen who actively participates in social life, while trying to improve it.
Keywords: development of the personality; physical training; culture; the historical aspect